Pelatihan Membaca Kitab Gundul dengan Teknik 234 untuk Peningkatan Kompetensi Guru Bahasa Arab di SMP Unggulan Amanatul Ummah Program Tahfidz Pacet Mojokerto - Muhammad Hafidz; Benny Angga Permadi (ABDIMASY: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PKM) aims to enhance the competence of Arabic language teachers in reading, understanding, and teaching kitab gundul through the implementation of Technique 234, also known as the Jie Sam Soe method. The program was conducted at SMP Unggulan Amanatul Ummah Tahfidz Program, Mojokerto, involving 20 Arabic language teachers. The implementation method consisted of five stages: introduction to the concept of kitab gundul, explanation of the theory of Technique 234, practice in reading classical texts, peer teaching, and competency evaluation through pre-tests and post-tests. The results showed an average increase of 30% in teachers’ ability to read kitab gundul, based on a comparison of pre-test and post-test scores. The teachers demonstrated high levels of enthusiasm, and a community of classical text learner-teachers was formed as a follow-up initiative. The application of Technique 234 proved effective in integrating nahwu and sharaf theory into practical Arabic text reading and in enhancing teachers’ confidence in teaching classical texts.